Increased expression of the mitochondrial derived peptide, MOTS-c, in skeletal muscle of healthy aging men is associated with myofiber composition - D’Souza, Randall F. (Aging (Albany NY), 2020)
Mitochondria putatively regulate the aging process, in part, through the small regulatory peptide, mitochondrial open reading frame of the 12S rRNA-c (MOTS-c) that is encoded by the mitochondrial genome. Here we investigated the regulation of MOTS-c in the plasma and skeletal muscle of healthy aging men. Circulating MOTS-c reduced with age, but older (70-81 y) and middle-aged (45-55 y) men had ~1.5-fold higher skeletal muscle MOTS-c expression than young (18-30 y). Plasma MOTS-c levels only correlated with plasma in young men, was associated with markers of slow-type muscle, and associated with improved muscle quality in the older group (maximal leg-press load relative to thigh cross-sectional area). Using small mRNA assays we provide evidence that MOTS-c transcription may be regulated independently of the full length 12S rRNA gene in which it is encoded, and expression is not associated with antioxidant response element (ARE)-related genes as previously seen in culture. Our results suggest that plasma and muscle MOTS-c are differentially regulated with aging, and the increase in muscle MOTS-c expression with age is consistent with fast-to-slow type muscle fiber transition. Further research is required to determine the molecular targets of endogenous MOTS-c in human muscle but they may relate to factors that maintain muscle quality.